Idiopathic short stature, current knowledge and perspectives – Review article - Rohde, Anna; Obara-Moszyńska, Monika (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Short stature (SS) is a frequent cause of referral to endocrine clinics and is also a widely researched condition in the literature. Idiopathic short stature (ISS) is diagnosed when a list of known causes of SS had been ruled out. The aim of this article is to draw attention of pediatricians to what is new in the ISS diagnosis and to introduce to the ISS problem some new entries which can be further researched if needed. It was a challenge to define and categorize ISS anew in the light of some substantial progress gained in this field in the last decade. The aforementioned progress pertains usually to one of the three following categories: (1) exposing underdiagnosed genetic syndromes with minimal dysmorphic features, for instance Noonan syndrome, SHOX deficiency or rasopathies and finding new mutations in known genes, (2) proving new strategies to identify genetic causes of short stature effective, especially the perspectives opened by whole exome sequencing (WES) which can well identify monogenic disorders known to cause growth disorders and; (3) approaches focused on metabolic or paracrine mechanisms, among them studies of ghrelin influence on height and vitamin D receptor gene polymorphisms in ISS patients, not forgetting simple but vital means as working in a multidisciplinary team. Clinicians caring for SS children are frequently in difficult diagnostic situation. Therefore reliable sources of reference and sharing of clinical experience are of great value in the diagnostic process of ISS.